Changing behaviour in pregnant women: A scoping review. (June 2020) - Zinsser, Laura A.; Stoll, Kathrin; Wieber, Frank; Pehlke-Milde, Jessica; Gross, Mechthild M.
Highlights: Education for knowledge gain is the form of intervention most often used for behaviour change. There is a need for behaviour change programmes during pregnancy that aim to empower women. Midwives should develop, manage, implement or support in behaviour change programmes during pregnancy. Abstract: Objectives: Behaviour change programmes (BCPs) for pregnant women are frequently implemented as part of health promotion initiatives. At present, little is known about the types of behaviour change programmes that are being implemented and whether these programmes are designed and delivered in accordance with the principles of high quality maternity care. In this scoping review, we provide an overview of existing interventions related to behaviour change in pregnancy with a particular emphasis on programmes that include empowerment components to promote autonomy and woman-led decision-making. Methods: A systematic search strategy was applied to check for relevant papers in August 2017 and again in October 2018. Results: Thirty studies met the criteria for inclusion. These studies addressed weight management, smoking cessation, general health education, nutrition, physical activity, alcohol consumption and dental health. The main approach was knowledge gain through education. More than half of the studies ( n = 17) included three or more aspects of empowerment as part of the intervention. The main aspect used to foster women`s empowerment was skills and competencies. In nine studies midwives were involved, but not as programme leaders. Conclusions: Education for knowledge gain was found to be the prevailing approach in behaviour change programmes. Empowerment aspects were not a specific focus of the behaviour change programmes. This review draws attention to the need to design interventions that empower women, which may be beneficial through their live. As midwives provide maternal healthcare worldwide, they are well-suited to develop, manage, implement or assist in BCPs.